Tactical And Technical Aspects of Surgical Interventions for Vental Hernias and Obesity - Rakhmanov Kosim Erdanovich; Davlatov Salim Sulaimanovich; Abdurakhmanov Diyor Shukurillaevich; Khidirov Ziyadulla Erkinovich (Periodica Journal, 2022)
Rationale. Simultaneous operations are a promising area of modern herniology. In this regard, the development of objective indications and contraindications for performing simultaneous interventions on the organs of the abdominal cavity and abdominal wall in patients with ventral hernia is extremely important and affects the approaches to the method of the proposed operation and the technique of its execution
Keywords: ventral hernias; obesity; hernioplasty; dermatolipidectomy